Use one equation to substitute into the other,then solve for a one variable problem. Use your new information (the solved variable) to solve for the second variable.
For the first set:
-3x - y = 2 rearranged becomes:
y = -3x -2
Using this "definition" of y, substitute it into the second equation as such:
-6x + 2(-3x -2) = -2
-6x - 6x - 4 = -2
-12x = 2
x = -1/6
Substitute -(1/6) for x in either equation to solve for y:
-3(-1/6) - y = 2
y = -3/2
Do the same for the second pair of equations to make sure you got it (the answers for x and y are x=9/7, y = 1/7).
2006-11-30 13:45:40
·
answer #1
·
answered by sep_n 3
·
0⤊
0⤋
QUESTION 1
(1) -3x-y=2
-3x = 2+y
(2) -6x+2y=-2
-6x= -2-2y
Multiply equation (1) by 2:
-3x = 2+y
-6x = 4+2y
Then, equate both equations to each other, since both equals to
-6:
4+2y=-2-2y
4y=-6
y= -(6/4)
Substitute y=-(6/4) into equation (1),
-3x-(-6/4)=2
-3x+(6/4)=2
(6/4)-2=3x
-(1/2)=3x
x=-(1/6)
QUESTION 2
(1)x+5y=2
x=2-5y
(2)x-1=2y
x=2y+1
Equate both equations to each other:
2-5y=2y+1
1=7y
y=1/7
Sub y=1/7, into equation 1:
x+5(1/7)=2
x+5/7=2
x= 9/7
2006-11-30 13:49:45
·
answer #2
·
answered by lee-wlcj 2
·
0⤊
0⤋
For the first one, all you need to do is isolate one of the variables, and then enter it into the other equation. For your first example
-3x - y = 2
-6x + 2y = -2
Let's isolate the y in the first equation. That'll give us
y = -3x - 2
If we plug this into the second equation, we get
-6x + 2(-3x-2) = -2
Now, we just solve for x.
-6x - 6x - 4 = -2
-12x - 4 = -2
-12x = 2
x = -1/6
To solve for y, we just put x = -1/6 into one of the equations.
-3(-1/6)-y = 2
1/2 - y = 2
y = 1/2 - 2 = -3/2
x = -1/6, y = -3/2
Now you try the same thing for the second one.
2006-11-30 13:40:20
·
answer #3
·
answered by Puggy 7
·
0⤊
0⤋
1)
in the first equation: y=-3x-2
substitute that into the second equation
-6x+2(-3x-2)=-2
-6x-6x-4=-2
-12x=2
x=-1/6
plug x into either of the original equations
-6(-1/6)+2y=-2
1+2y=-2
y=-3/2
so the solution is (-1/6,-3/2)
use the same method on #2
2006-11-30 13:39:46
·
answer #4
·
answered by Greg G 5
·
1⤊
0⤋
y=-3x-2 -6x-6x-4=-2 -12x=2 x= -1/6 y= -3/2
x=2-5y 2-5y-1=2y 7y=1 y=1/7 x=9/7
2006-11-30 13:53:25
·
answer #5
·
answered by e a 1
·
0⤊
0⤋
multiply -3x-y=2 by 2, you will get -6x-2y=4
let -6x-2y=4 is equation 1
let -6x+2y=-2 is equation 2
equation 1 plus equation 2
-12x = 2
x = -1/6
substitute x = -1/6 to equation 1, you will get y = -3/2
let x+5y=2 be equation 3
let x-2y=1 be quation 4
equation 3 minus equation 4
7y = 1
y = 1/7
substitute y = 1/7 to equation 3
x = 9/7
2006-11-30 13:45:37
·
answer #6
·
answered by csp 2
·
0⤊
0⤋
To sove by substitution, solve for x in terms of y from one of the equations, put that expression in for x in the other. What you have then is one equation in y which you can solve directly. When you get that value of y, put it into either equation to get x.
Example: in your first set, -3x-y=2, so x = (y-2)/3. Put this in for x in -6x+2y=-2: -6(y-2)/3+2y=-2, etc.
2006-11-30 13:41:00
·
answer #7
·
answered by gp4rts 7
·
0⤊
0⤋